2016
DOI: 10.3762/bjoc.12.25
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective palladium-catalyzed ring-opening reactions of C1-substituted oxabicyclo[2,2,1]hepta-2,5-diene-2,3-dicarboxylates

Abstract: SummaryPalladium-catalyzed ring-opening reactions of C1 substituted 7-oxanorbornadiene derivatives with aryl iodides were investigated. The optimal conditions for this reaction were found to be PdCl2(PPh3)2, ZnCl2, Et3N and Zn in THF. Both steric and electronic factors played a role in the outcome of the reaction as increasing the steric bulk on the bridgehead carbon decreased the yield. These reactions were found to be highly regioselective, giving only one of the two possible regioisomers in all cases. A div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…In past years, our research group (Ballantine et al, 2009;Edmunds et al, 2015;Hill & Tam, 2019;Edmunds et al, 2016;Raheem et al, 2014) has investigated the effects of various C 1 -substituted oxabenzonorbornadienes (OBD) on controlling the regioselectivity of ring-opening reactions. In 2015, Nagamoto and Nishimura reported the iridiumcatalysed hydroacylation reaction of bicyclic alkenes with 2-hydroxybenzaldehyde and its derivatives.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…In past years, our research group (Ballantine et al, 2009;Edmunds et al, 2015;Hill & Tam, 2019;Edmunds et al, 2016;Raheem et al, 2014) has investigated the effects of various C 1 -substituted oxabenzonorbornadienes (OBD) on controlling the regioselectivity of ring-opening reactions. In 2015, Nagamoto and Nishimura reported the iridiumcatalysed hydroacylation reaction of bicyclic alkenes with 2-hydroxybenzaldehyde and its derivatives.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…In past years, our research group has investigated the effects of various C 1 -substituted oxabenzonorbornadienes (OBDs) on controlling the regioselectivity of ring-opening reactions (Ballantine et al, 2009;Edmunds et al, 2015Edmunds et al, , 2016Raheem et al, 2014). Very recently, Yang et al (2019) reported the first iridium-catalysed ring-opening reaction of oxa/aza benzonorbornadienes with various alcohol nucleophiles.…”
Section: Structure Descriptionmentioning
confidence: 99%